Mechanistic insights into the biological activity of S-Sulfocysteine in CHO cells using a multi-omics approach - Nguyen, Melanie; Le Mignon, Maxime; Schnellbächer, Alisa; Wehsling, Maria; Braun, Julian; Baumgaertner, Jens; Grabner, Martina; Zimmer, Aline (Frontiers in Bioengineering and Biotechnology, 2023)
S-Sulfocysteine (SSC), a bioavailable L-cysteine derivative (Cys), is known to be taken up and metabolized in Chinese hamster ovary (CHO) cells used to produce novel therapeutic biological entities. To gain a deeper mechanistic insight into the SSC biological activity and metabolization, a multi-omics study was performed on industrially relevant CHO-K1 GS cells throughout a fed-batch process, including metabolomic and proteomic profiling combined with multivariate data and pathway analyses. Multi-layered data and enzymatical assays revealed an intracellular SSC/glutathione mixed disulfide formation and glutaredoxin-mediated reduction, releasing Cys and sulfur species. Increased Cys availability was directed towards glutathione and taurine synthesis, while other Cys catabolic pathways were likewise affected, indicating that cells strive to maintain Cys homeostasis and cellular functions.